Characterizing Pastoral Care Utilization by Cancer Patients. (July 2021) - Hyer, J. Madison; Paredes, Anghela Z.; Kelley, Elizabeth Palmer; Tsilimigras, Diamantis; Meyer, Bonnie; Newberry, Hanci; Pawlik, Timothy M.
Purpose: To assess the rate of and characterize the utilization of pastoral care (PC) among patients on their cancer treatment trajectory. Methods: Patients included in the present study were diagnosed with cancer 01/2015-08/2019 at The Ohio State Wexner Medical Center—The James. To determine which patient demographic and clinical factors were independently associated with PC utilization, a multivariable logistic regression was performed. Results: A total of 14, 322 patients were included in the study and 5, 166 (36.1%) had at least one visit with PC. Cancers such as brain (n = 232, 4.5% vs. n = 159, 1.7%), liver/pancreas (n = 733, 14.2% vs. 686, 7.5%), and lung (n = 1, 288 vs. 24.9% vs. n = 1, 113, 12.2%) were more commonly noted among patients who utilized PC services (all p < 0.001). Furthermore, compared with patients diagnosed with Stage 1 cancer, patients with more advanced disease stages had higher odds of utilizing PC services (Stage III: OR 2.37, 95% CI 2.07-2.70; Stage IV OR 2.31, 95% CI: 2.04-2.61; both p < 0.05). Interestingly, patients who had a DNR order had a markedly higher odds (OR 4.18, 95%CI 3.76-4.65, p < 0.001) of utilizing PC services. Discussion: One in three patients with cancer utilized PC services. Patients with more severe prognoses and individuals with a DNR order were more likely to utilize PC. The data suggest that PC services are an important resource for many patients and should be integrated into the treatment approach for cancer.